ACHIEVEMENTS OF THE UNIVERSITY OF WORLD ECONOMY AND DIPLOMACY (UWED), TASHKENT, UZBEKISTAN (2023–2025) (Web of Teachers: Inderscience Research, 2026)
The University of World Economy and Diplomacy (UWED), established on September 23, 1992, in Tashkent, is Uzbekistan’s premier public institution specializing in international economics, diplomacy, international law, and global relations. Functioning under the Ministry of Foreign Affairs of the Republic of Uzbekistan, UWED has a mission to train highly qualified specialists geared toward supporting Uzbekistan’s foreign policy, economic diplomacy, and leadership roles on the global stage.